Integrating Religious Moderation Into Islamic Education: Curriculum Development For Tolerance And Inclusivity - Nur 'Azah; Muh Ibnu Sholeh (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
: Religious moderation has emerged as an essential paradigm for fostering tolerance and inclusivity in multicultural societies, particularly within Islamic education. This study explores the integration of religious moderation values into Islamic education curricula to strengthen students’ capacity for empathy, respect, and interfaith harmony. Using a qualitative descriptive-analytical method, this research synthesizes findings from relevant literature, policy documents, and case studies in Islamic educational institutions across Southeast Asia. The results indicate that incorporating religious moderation into curriculum design positively influences students’ attitudes toward diversity and minimizes tendencies toward radicalism and intolerance. The study highlights three strategic dimensions: (1) embedding moderation principles into learning objectives and content, (2) employing student-centered pedagogical approaches that encourage dialogue and critical thinking, and (3) implementing institutional policies that promote inclusivity and equality. By adopting a comprehensive framework, Islamic education can serve as a transformative platform for cultivating open-mindedness and social cohesion. The findings contribute to contemporary discourse on curriculum reform and provide practical implications for educators, policymakers, and curriculum developers aiming to nurture a generation grounded in tolerance and religious harmony.